2019
DOI: 10.1038/s41598-019-54502-6
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis sheds light on intracellular signaling cascades triggered by Formyl-Peptide Receptor 2

Abstract: Formyl peptide receptors (FPRs) belong to the family of seven transmembrane Gi-protein coupled receptors (GPCR). FPR2 is considered the most promiscuous member of this family since it recognizes a wide variety of ligands. It plays a crucial role in several physio-pathological processes and different studies highlighted the correlation between its expression and the higher propensity to invasion and metastasis of some cancers. FPR2 stimulation by its synthetic agonist WKYMVm triggers multiple phosphorylations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 81 publications
4
62
1
Order By: Relevance
“…Previously, we applied a phospho-proteomics approach to analyse phosphorylated proteins in WKYMVm-stimulated CaLu-6 cells and identified 290 phosphoproteins and 53 unique phospho-peptides mapping on 40 proteins [ 56 ]. We also demonstrated that the selective phosphorylation on Ser82 of HSP-27, Ser339 of OSR1, and Ser170 of MARCKS uniquely depends on FPR2 stimulation by WKYMVm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we applied a phospho-proteomics approach to analyse phosphorylated proteins in WKYMVm-stimulated CaLu-6 cells and identified 290 phosphoproteins and 53 unique phospho-peptides mapping on 40 proteins [ 56 ]. We also demonstrated that the selective phosphorylation on Ser82 of HSP-27, Ser339 of OSR1, and Ser170 of MARCKS uniquely depends on FPR2 stimulation by WKYMVm.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated a potential FPR2 homodimerization upon WKYMVm stimulation, which indicates the triggering of anti-inflammatory signals; moreover, we showed that stimulation of CaLu-6 cells with ANXA1 induces HSP-27(S82), OSR1(S339), and MARCKS(S170) phosphorylation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations